A Balthasarian ‘Ecclesiology’: Apprehending the Church with an Ecclesial Aesthetics - Kristiatmo, Thomas (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2011)
Ecclesiology might have put the center of its gravity on the modern rationality. As a result, this kind of ecclesiology might overlook the mystical yet beautiful side of the church, which seem to have a more unifying character to the already divided church. This article wants to explore with Hans Urs von Balthasar’s theology of aesthetics the origin and the characteristics of the church from the people around Jesus, the event of the cross, the form of revelation, the Eucharist, the sacrament, and the way of love. This sort of an ecclesial aesthetics is one of the different ways of apprehending the church. This way might contribute to the traditional understanding of the church that has been characterized with modern logical concepts. Balthasar is offering the way of apprehending the church through the pulchrum toward the more unifying engagement with the mystery of God, the revelation of God through Jesus Christ. Keywords:*Ecclesiology, *rationality, *beauty, *mystical theology, *form of revelation, *the way of love, *ecclesial aesthetics, *bonumet verum